Divergence? What Divergence? - Charles Wyplosz (Intereconomics, 2019)
The joint Intereconomics/CEPS conference focused on income convergence among EU countries and within specific countries like Germany and Italy. I would like to first caution about overinterpreting these results and then look at other divergences within the Eurozone, which I regard as much more important.
Keywords: 330; Economic convergence; Labour markets; Macroeconomic imbalances